Identifikasi Modal Sosial Dalam Peningkatan Mutu Madrasah Tsanawiyah Negeri 1 Kabupaten Kaur Provinsi Bengkulu - Haryanto; Danim, Sudarwan; Somantri , Manap (UNIVERSITAS BENGKULU, 2024)
This research aims to describe the results of identifying social capital in improving quality of State Madrasah Tsanawiyah 1 Kaur. The research uses qualitative descriptive methods. Research subjects were the principal, deputy principal, teachers, staff and community leaders at state MTs 1 Kaur. Research data was obtained from interviews, observation and documentation. Research data analysis includes data reduction, data presentation, verification and drawing conclusions. Research results show that the importance of social capital as a determining factor in improving the quality of education needs to be done by exploring, developing and optimizing social capital as a strategic key to improving the quality of education at state MTs 1 Kaur.